Health and well-being in the social representations of health professionals in selected Latin American countries 2019–2020 - Hernández-Garnica , Clotilde; Suárez-Lugo, Nery de la Concepcion (Horizonte Sanitario, 2023)
Objectives: The research proposed three objectives: to describe the social representation of health and well-being; characterize the work of health professionals to promote well-being; establish similarities and differences between what they know and do, with respect to the concept of the World Health Organization.Materials and methods: It is a descriptive, cross-sectional, multicenter study (Cuba, Mexico, Panama and Peru); after a literature review, a survey and expert consultation were carried out. Non-probabilistic sampling was used and descriptive statistical analyzes were performed.Results: The health professionals, perceive well-being as very pleasant and comfortable, possible, sweet, good, responsible, flexible, safe, white, somewhat light, but a bit short and difficult; health is perceived as very pleasant, possible, comfortable, flexible, sweet, responsible, safe, good, white, light and long but difficult; most believe they know the concepts of health and well-being of WHO/PAHO, but when compared to those established by these organizations, they are not correct or complete, and their knowledge is insufficient.Conclusions: In conclusion, they do not have a full understanding of the relationship between both concepts; most take actions to promote well-being that are easy for them; they are not perceived as active and transforming entities in the activities that generate a healthy life and therefore, they are not in line with the necessary transformations that privilege health and well-being.Keywords: Health professionals; Health; Welfare; Social; Representation